2021
DOI: 10.1101/2021.04.26.440975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell dissection of the human cerebrovasculature in health and disease

Abstract: SummaryDespite the importance of the blood-brain barrier in maintaining normal brain physiology and in understanding neurodegeneration and CNS drug delivery, human cerebrovascular cells remain poorly characterized due to their sparsity and dispersion. Here, we perform the first single-cell characterization of the human cerebrovasculature using both ex vivo fresh-tissue experimental enrichment and post mortem in silico sorting of human cortical tissue samples. We capture 31,812 cerebrovascular cells across 17 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 75 publications
(29 reference statements)
3
17
0
Order By: Relevance
“…The MHC class II signature was upregulated in all pathologies according to the pattern described above showing highest expression levels at the level of large veins, veins>large arteries and arteries (Figure 5c,g,h, Extended Data Figures 32 and 28 ). We observed a partial overlap of the MHC class II and peripheral signatures and of the BBB dysfunction module with a common predominance in large caliber vessels, but a more widespread/stronger expression of the peripheral signature and BBB dysfunction module in angiogenic capillaries (Extended Data Figures 33,34), in line with the previously-observed links between BBB dysregulation and innate immune activation 44 . Together, these data suggest that pathological CNS ECs upregulate MHC class II receptors in brain tumors and brain vascular malformations.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The MHC class II signature was upregulated in all pathologies according to the pattern described above showing highest expression levels at the level of large veins, veins>large arteries and arteries (Figure 5c,g,h, Extended Data Figures 32 and 28 ). We observed a partial overlap of the MHC class II and peripheral signatures and of the BBB dysfunction module with a common predominance in large caliber vessels, but a more widespread/stronger expression of the peripheral signature and BBB dysfunction module in angiogenic capillaries (Extended Data Figures 33,34), in line with the previously-observed links between BBB dysregulation and innate immune activation 44 . Together, these data suggest that pathological CNS ECs upregulate MHC class II receptors in brain tumors and brain vascular malformations.…”
Section: Resultssupporting
confidence: 88%
“…In brain pathologies, we found that the MHC class II signature was highest in brain vascular malformations (CAV>AVM), the extra-axial brain tumor MEN, the intra-axial secondary brain tumor MET, followed by the intra-axial primary brain tumors HEM>LGG>GBM, TL and TLadjCAV and the fetal brain, grossly following the peripheral signature expression gradient whereas the CNS signature showed an inverse trend The MHC class II signature was upregulated in all pathologies according to the pattern described above showing highest expression levels at the level of large veins, veins>large arteries and arteries (Figure 5c,g,h, Extended Data Figures 32 and 28 ). We observed a partial overlap of the MHC class II and peripheral signatures and of the BBB dysfunction module with a common predominance in large caliber vessels, but a more widespread/stronger expression of the peripheral signature and BBB dysfunction module in angiogenic capillaries (Extended Data Figures 33,34), in line with the previously-observed links between BBB dysregulation and innate immune activation 44 . Together, these data suggest that pathological CNS ECs upregulate MHC class II receptors in brain tumors and brain vascular malformations.…”
Section: Alteration Of Cns-specificity In Pathological Brain Vascular Endothelial Cellssupporting
confidence: 88%
See 3 more Smart Citations